INDICATORS AND CONDITIONS ASSOCIATED WITH SUCCESSFUL AGING: AN INTEGRATIVE LITERATURE REVIEW - Maria das Graças Melo Fernandes; Antonia Oliveira Silva; Lara de Sá Neves Loureiro; Ana Claúdia Torres Medeiros (Universidade Federal do Paraná, 2011)
the objective of this study was to study, by means of an integrative literature review, the scientific knowledge produced between 2003 and 2010 concerning indicators and conditions associated with successful aging. Twenty articles were selected for the review. Concerning authors' origin, it was noted that 60% of the articles were written by Brazilians, followed by North Americans (25%). Concerning the type of periodical, those of multidisciplinary character predominated (50%) with nurses foremost among the authors, followed by doctors (30%) and psychologists (20%). Concerning the level of evidence referred to in the articles, the majority (45%) presented level four evidence. The knowledge produced revealed that successful aging is a phenomenon which is determined by positive bio-psychosocial, cultural and spiritual conditions, and is evidenced by a good state of health, functional physical, mental and social abilities, autonomy, a sense of self-efficacy, self-esteem and satisfaction with life.